استخدام التعليم الإلكتروني في عملية التعليم بالجامعات والمدارس - Badruzzaman, Badruzzaman (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2021)
To conduct the education process during the Corona pandemic, universities and schools benefited from educational technology. This research aims to identify the benefit of educational technology, the so-called e-learning, in the education process. As for the method of this research, it is a descriptive and analytical approach when the researcher analyzes the various teory related to e-learning in the education process. The results of the research are that e-learning helps the teacher and students in the education process during the Corona pandemic. E-learning does not eliminate the role of the teacher, but rather his role becomes more important.